Складові розвитку сільських територій - Шебештень Едіна; Sebestyén Edina; Edina Shebestyen (Львівський університет бізнесу та права, 2022)
Резюме. В статті обґрунтовано основні структурні елементи розвитку сільських територій: територіальні громади, місцевий бізнес і громадянське суспільство. Доведено їх взаємозв’язок, що реалізується реформою децентралізації. Досліджено основні умови ефективного функціонування сільських територій, серед яких створення безбар’єрного середовища в межах сільських територій; трансформування сільських територій у відповідності до цілей Європейського зеленого курсу; покращення інфраструктури сільських територій. Доведено необхідність покращення інфраструктури сільських територій, що націлене на зниження рівня безробіття і залучення молоді до розвитку села, підвищення якості й доступності медицини та освіти, підтримки пайовиків, започаткування та активний розвиток кооперативного руху. Обов‘язковою умовою розвитку сільських територій є вплив різних суб’єктів: підприємців (виробники, фермери тощо); інвесторів (вітчизняні та зарубіжні); державних структур. Доведено вплив підприємців на розвиток сільських територій, оскільки саме вони вносять свій значний вклад в податок територіальних громад. Обґрунтовано вплив інвесторів на розвиток сільських територій, які забезпечують ефективне функціонування й розвиток агропідприємств, оскільки інвестиційні ресурси сприяють зростанню результативності сільського господарства, нарощуванню обсягів їх виробництва та збільшенню виробничого потенціалу підприємства. Встановлено необхідність підтримки держави у розвитку сільських територій. Держава забезпечує процес виявлення проблем, розробку та реалізацію нових та існуючих цільових програм сільського розвитку. Доведено, що сільські території є невід’ємною частиною успішної економіки України як аграрної держави.

Abstract. The article substantiates the main structural elements of the development of rural areas: territorial communities, local businesses, and civil society. Their relationship, implemented by the decentralization reform, is proven. The primary conditions for the effective functioning of rural areas have been studied, including creating a barrier-free environment within rural areas, transforming rural areas by the goals of the European Green Course, and improving the infrastructure of rural areas. The improvement of the infrastructure of rural areas aimed at reducing the level of unemployment and involving young people in the development of the village, improving the quality and availability of medicine and education, supporting shareholders, and the initiation and active development of the cooperative movement have been proven. A prerequisite for developing rural areas is the influence of various subjects: entrepreneurs (producers, farmers, etc.); investors (domestic and foreign); state on its activities. The impact of entrepreneurs on the development of rural areas has been proven, after which they contribute to the data of territorial communities. The influence of investors on the development of rural areas, which ensures the effective functioning and development of agricultural enterprises, is substantiated. Additional investment resources contribute to the growth of agricultural productivity, increasing the volume of their production and increasing the production potential of the enterprise. Provision of state support in the development of rural areas has been established. The state ensures the problem identification, development, and implementation of new and existing rural development target programs. It has been proven that rural areas are an integral part of the booming economy of Ukraine as an agricultural state. That is why the support of rural residents and the promotion of village development is a priority for state and local bodies.
Components of the development of rural areas
Редакційна колегія: https://nzlubp.org.ua/index.php/journal/about/editorialTeam
Зміст: https://nzlubp.org.ua/index.php/journal/issue/view/19
Keywords: децентралізація; територіальні громади; місцевий бізнес і громадянське суспільство; сільські території; decentralization; territorial communities; local business; civil society; rural areas